Knee Abduction Affects Greater Magnitude of Change in ACL and MCL Strains Than Matched Internal Tibial Rotation In Vitro. Issue 10 (October 2017) - Bates, Nathaniel A.; Nesbitt, Rebecca J.; Shearn, Jason T.; Myer, Gregory D.; Hewett, Timothy E.
Abstract: Background: Anterior cruciate ligament (ACL) injures incur over USD 2 billion in annual medical costs and prevention has become a topic of interest in biomechanics. However, literature conflicts persist over how knee rotations contribute to ACL strain and ligament injury. To maximize the efficacy of ACL injury prevention, the effects of underlying mechanics need to be better understood. Questions/purposes: We applied robotically controlled, in vivo‐derived kinematic stimuli to the knee to assess ligament biomechanics in a cadaver model. We asked: (1) Does the application of abduction rotation increase ACL and medial collateral ligament (MCL) strain relative to the normal condition? (2) Does the application of internal tibial rotation impact ACL strain relative to the neutral condition? (3) Does combined abduction and internal tibial rotation increase ligament strain more than either individual contribution? Methods: A six‐degree‐of‐freedom robotic manipulator was used to position 17 cadaveric specimens free from knee pathology outside of low‐grade osteoarthritis (age, 47 ± 8 years; 13 males, four females) into orientations that mimic initial contact recorded from in vivo male and female drop vertical jump and sidestep cutting activities. Four‐degree rotational perturbations were applied in both directions from the neutral alignment position (creating an 8° range) for each frontal, transverse, and combined planes while ACL and MCL strains were continuously recorded with DVRT strain gauges implanted directly on each ligament. Analysis of variance models with least significant difference post hoc analysis were used to assess differences in ligament strain and joint loading between sex, ligament condition, or motion task and rotation type. Results: For the female drop vertical jump simulation in the intact knee, isolated abduction and combined abduction/internal rotational stimuli produced the greatest change in strain from the neutral position as compared with all other stimuli within the ACL (1.5% ± 1.0%, p ≤ 0.035; 1.8% ± 1.3%, p ≤ 0.005) and MCL (1.8% ± 1.0%, p < 0.001; 1.6% ± 1.3%, p < 0.001) compared with all other applied stimuli. There were no differences in mean peak ACL strain between any rotational stimuli (largest mean difference = 2.0%; 95% confidence interval [CI], −0.9% to 5.0%; p = 0.070). These trends were consistent for all four simulated tasks. Peak ACL strain in the intact knee was larger than peak MCL strain for all applied rotational stimuli in the drop vertical jump simulations (smallest mean difference = 2.1%; 95% CI, −0.4% to 4.5%; p = 0.047). Conclusions: Kinematically constrained cadaveric knee models using peak strain as an outcome variable require greater than 4° rotational perturbations to elicit changes in intraarticular ligaments. Clinical Relevance: Because combined rotations and isolated abduction produced greater change in strain relative to the neutral position for the ACL and MCL than any other rotational stimuli in this cadaver study, hypotheses for in vivo investigations aimed toward injury prevention that focuses on the reduction of frontal plane knee motion should be considered. Furthermore, reduced strain in the MCL versus the ACL may help explain why only 30% of ACL ruptures exhibit concomitant MCL injuries.